Covid-19 revolutionising higher education: An educator’s viewpoint of the challenges, benefits and the way forward - Cheema, Manraj Singh (Life Sciences, Medicine and Biomedicine, 2020)
The global COVID-19 pandemic has radically change the higher education landscape that caused closures of all education institutions in adherence to social distancing. It has forced the education sector to adopt online teaching and learning, and reminded educators that a flexible and robust education system is needed as the future is unpredictable. This paper focuses on educator’s viewpoint in adapting and adopting online teaching and learning, highlights the challenges experienced and the ways to overcome it that could serve as a reference for other educators to assimilate in similar circumstances. This paper also explores and discusses the benefit brought by these changes to higher education and the way forward in progressing, revolutionising and sustaining quality online teaching and learning where globalised, borderless and seamless teaching and learning with technology may become “the new normal” in higher education.